EFFECT OF WORK DISCIPLINE AND WORK FACILITIES ON EMPLOYEE PERFORMANCE (Survey at Bangkinang, Airtiris and Lipat Kain) - Egi Afifah; Arman Arman; Supardi Supardi (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine work discipline and work facilities on employee performance (Survey at the Bangkinang, Airtiris and Lipat kain) the analysis used in this study is multiple linear analysis, with the number of respondents as many as 40 people, hypothesis testing is carried out with the F test and t test with alpha 5% or 95% confidence level.Based on the results of the study, it can be concluded that the variables of work discipline and work facilities have a significant effect on the performance of the employees of the Bangkinang, Airtiris and Lipat Kain Post offices both simultaneously and partially.This is evident from the test results. F and t test at 95% confidence level.Work Discipline variable is the dominant factor influencing the performance of Bangkinang, Airtiris and Lipat Kain Post office employees, because the Work Discipline variable has a larger regression coefficient than the other variables.Work Discipline Variable (X₁) and Work Facilities (X₂) with Employee Performance ( Y) has a relationship of 87.7%. Thus, if the variables of Work Discipline (X₁) and Work Facilities (X₂) change, the Employee Performance (Y) will also change. Variations up or down in employee performance by 76.8% are determined by the variables of Work Discipline (X₁) and Work Facilities (X₂), while the remaining 23.2% of employee performance is determined by other factors outside the model.